Roles of 670 nm Photobiomodulation on Rat Anterior Ischemic Optic Neuropathy: Enhancing RGC Survival, Mitochondrial Function, and Anti-Inflammatory Response - Tu-Wen Chen; Yao-Tseng Wen; Pei-Kang Liu; Monir Hossen; Rong-Kung Tsai (Antioxidants, 2025)
Non-arteritic anterior ischemic optic neuropathy (NAION) leads to retinal ganglion cell (RGC) loss and visual impairment, with no effective treatment. This study investigated the neuroprotective effect of 670 nm photobiomodulation (PBM) in a rat NAION model (rNAION). Wistar rats received 670 nm light exposure (10-min, 3000 lux) twice daily for 3 days after rAION injury, followed by 4 days of light treatment once a day. This study evaluated the neuroprotective effects of 670 nm light in an rNAION model. Rats received 670 nm light therapy (10 min/day, 3000 lux) for seven days post-injury. Treatment improved visual function (a 3.36-fold increase in FVEP amplitude), enhanced RGC survival (1.55-fold), and reduced apoptosis (a 15.86-fold reduction in TUNEL-positive cells). Inflammatory cytokines and ED1+ macrophage infiltration were significantly decreased. Oxidative stress was attenuated, with increased ATP, Nrf2, and PGC-1α levels and improved mitochondrial dynamics. These findings support 670 nm light as a potential therapy for NAION.